2005
DOI: 10.1007/bf03404029
|View full text |Cite
|
Sign up to set email alerts
|

Rationale to Evaluate Medically Supervised Safer Smoking Facilities for Non-injection Illicit Drug Users

Abstract: Many cities are experiencing ongoing infectious disease epidemics and substantial community harm as a result of illicit drug use. In an effort to reduce these public order and public health concerns, consideration has been given to the opening in Vancouver of a safer smoking facility (SSF). The present review was conducted to examine if there is a rationale to support the evaluation of a SSF in the Canadian context. Available evidence suggests that conventional drug control strategies are insufficient to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 46 publications
0
19
0
2
Order By: Relevance
“…With respect to our study setting, it should be noted that drug use and associated high‐risk behaviours are deeply entrenched among IDU and other polydrug‐using subpopulations. Further, previous research in our study setting has demonstrated the limited ability of stand‐alone public health interventions to adequately modify high‐risk behaviours and we therefore conclude that a range of interventions may be required to successfully reduce the incidence of polydrug use and its related public health and public order harms [8,26,27].…”
Section: Discussionmentioning
confidence: 73%
“…With respect to our study setting, it should be noted that drug use and associated high‐risk behaviours are deeply entrenched among IDU and other polydrug‐using subpopulations. Further, previous research in our study setting has demonstrated the limited ability of stand‐alone public health interventions to adequately modify high‐risk behaviours and we therefore conclude that a range of interventions may be required to successfully reduce the incidence of polydrug use and its related public health and public order harms [8,26,27].…”
Section: Discussionmentioning
confidence: 73%
“…Acquisition of HCV is rapid following initiation of IDU and of injecting paraphernalia (21,22). In addition, noninjection smoking paraphernalia has been implicated in HCV transmission (23). Given the risk of HCV morbidity and the high costs of treating HCV among injection drug users (see 'Economic impact'), evidence-based harmreduction strategies should be implemented (23)(24)(25)(26).…”
Section: Epidemiology Of Hiv and Hcv Coinfection Epidemiologymentioning
confidence: 99%
“…In addition, noninjection smoking paraphernalia has been implicated in HCV transmission (23). Given the risk of HCV morbidity and the high costs of treating HCV among injection drug users (see 'Economic impact'), evidence-based harmreduction strategies should be implemented (23)(24)(25)(26). Given the high rate of ongoing drug use during periods of incarceration, often associated with elevated risks of needle sharing, harm-reduction strategies for incarcerated individuals should also be considered (27)(28)(29).…”
Section: Epidemiology Of Hiv and Hcv Coinfection Epidemiologymentioning
confidence: 99%
“…L'acquisition du VHC est rapide chez les nouveaux UDI qui commencent à utiliser du matériel d'injection (21,22). De plus, des accessoires liés à l'inhalation qui ne sont pas utilisés pour les injections, ont déjà contribué à la transmission du VHC (23). Étant donné le risque de morbidité du VHC et le coût élevé des traitements du VHC chez les UDI (voir « L'impact sur l'économie de la santé », ci-dessous), il faudrait adopter des stratégies de réduction des méfaits fondées sur des données probantes (23)(24)(25)(26).…”
Section: Introductionunclassified
“…De plus, des accessoires liés à l'inhalation qui ne sont pas utilisés pour les injections, ont déjà contribué à la transmission du VHC (23). Étant donné le risque de morbidité du VHC et le coût élevé des traitements du VHC chez les UDI (voir « L'impact sur l'économie de la santé », ci-dessous), il faudrait adopter des stratégies de réduction des méfaits fondées sur des données probantes (23)(24)(25)(26). Compte tenu du taux élevé d'usage de drogues injectables qui se poursuit pendant les périodes d'incarcération, souvent associé à des risques élevés de partage d'aiguilles, il faudrait également adopter des stratégies de réduction des méfaits auprès des personnes incarcérées (27)(28)(29).…”
Section: Introductionunclassified